Synthesis of cyclical diamine templated uranium sulfates - Norquist, A; Thomas, P; Doran, M; O'Hare, D (2002)
The hydrothermal synthesis of uranium sulfates in the presence of a series of structurally related organic templating agents has been investigated. Piperazine, 2-methylpiperazine, and 1,4-diazabicyclo [2.2.2] octane, each of which is based upon the same six-membered cyclical diamine, exhibit different point symmetries and hydrogen-bonding characteristics. Small changes in the template structure result in marked differences in the reaction product. Three new compounds were synthesized and structurally characterized, [N2C4H12][UO2(H2O) (SO4)2], [N2C5H14][UO2(H2O) (SO4)2], and [N2C6H14][UO2(H2O) (SO4)2]. The inorganic framework of each compound was found to be dependent on the template structure. [N2C4H12][UO2(H2O) (SO4)2] consists of one-dimensional [UO2(H2O)(SO4)4/2] ∞2- chains, which hydrogen bond to one another to form quasi two-dimensional layers. One-dimensional chains are observed in [N2C5H14]- [UO2(H2O)(SO4)2]. These chains, which have the formula [UO2(H2O)(SO4)4/2(UO2 (H2O)(SO4)2)]∞4- are unprecedented in uranium chemistry. Two-dimensional layers are observed in [N2C4H12]- [UO2(H2O)(SO4)2]. Each uranyl [UO2]2- unit is bound to one water molecule and four bridging sulfate tetrahedra.